Keteladanan Ta’dib dan Sufistik Kiai Hasan Sepuh dalam Membentuk Spiritualitas dan Akhlak Santri di Pondok Pesantren Zainul Hasan Genggong - Fitri Fitri; Fathullah Rusly; Saiful Islam (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2026)
This study aims to analyze the exemplary values of ta’dib and Sufistic practices of Kiai Hasan Sepuh in shaping the spirituality and noble character of santri at Pondok Pesantren Zainul Hasan Genggong. This research employed a qualitative approach with a figure study within a case study framework. Data were collected through observation, in-depth interviews, and documentation, then analyzed using descriptive-analytical techniques. The findings indicate that the values of ta’dib are reflected in discipline, respect for knowledge, and ethical interaction, while Sufistic values are manifested through sincerity (ikhlāṣ), patience (ṣabr), humility (tawāḍu‘), and simplicity. The internalization process of these values occurs through habituation, the role of the kiai’s successors, and spiritual practices rooted in pesantren traditions. Supporting factors include the religious culture of the pesantren and the emotional closeness between kiai and santri, whereas modernization and social media become inhibiting factors in the transmission of values. This study concludes that the integration of ta’dib and Sufistic values through the exemplary legacy of Kiai Hasan Sepuh contributes significantly to shaping santri spirituality and moral character, as well as offering a relevant model for Islamic character education in the contemporary era.